Mechanical and Physical properties of Medium Density fiber board made from rice husk and fiber coating. - Majeed, Nagheen Abdul Jaleel Abdul; Jabber, Mohamed Ali; Al-jabire, Nooraldeen A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The study includes the preparation of Medium Density fiber board(MDF) made from the coating paper and rice husk, which are used in the prefabricated furniture panels, and manufacturing of these panels using PVA polymer as bonding materials. The flexural strength reach 3.73 MP compared with imported panels of 3.5 MP, thus these manufactured panels are resistant to combustion. The present study used rise husk with coating paper at different rate in addition to cement and polymer materials consist of poly vinyl estate (PVA). In this paper physical and mechanical peoperties of MDF manufacturer from natural fiber studied. Experimental results show that the density of MDF are about 339 to 820 Kg/m3. The Bending test are about 0.25 to 3.73 MP. The water absorption are about 4% to 24%.
Keywords: Rice husk; coating paper; cement; poly vinyl estate